(untitled) (Bangladesh Journal of Medical Education, 2018)
The present study was conducted amongst fourth and fifth year MBBS students of six medical colleges (4 govt. & 2 nongovt.) of Bangladesh to study their views regarding hidden curriculum and its effects on students learning in undergraduate medical education. A total of 637 students were included in the study. Out of 637 students, 393(61.7%) were female and 244(38.3%) male students. Three hundred and fifty (54.95%) were from fourth year and 287(45.05%) students were from fifth year MBBS. Most of the students (96.7%) agreed that teachers’ good behavior with students influences students’ active participation in the class. The mean score was highly satisfactory(mean 4.68 ± 0.643). Of the total responded students, 58.9% strongly agreed that teachers’ good behavior with parents influences students to do the same, and mean score was highly satisfactory. More than 87% agreed that teachers’ good behavior with colleagues influence students to do so. The mean score was 4.40 ± 0.730 and it was also highly satisfactory. Around 70% of the students strongly agreed that teachers’ good behavior with the patients and attendances influences students to maintain similar behavior and attitude with the patients and attendances. The mean score was 4.64 ± 0.643. As per views’ of the students, teachers’ depth of knowledge, devotion to the work, interest in the subject, honesty, fairness, teachers’ language and art of expression also affects students learning. The mean score was more than four as opined by the students in favor of institutional educational environment, cultural norms, values, traditions all of which can affect students’ learning. Teachers’ humiliation of the students, gender discriminations, social class difference, and students’ politics in the institutes all can affect students’ learning badly. After data analysis it was observed that many of the hidden factors normally exists in the institutes that affect students’ learning positively and others affect negatively. Bangladesh Journal of Medical Education Vol.9(1) 2018: 2-6